The Impact of Failures and Successes on Affect and Self-Esteem in Young and Older Adults - Rosi, Alessia; Cavallini, Elena; Gamboz, Nadia; Vecchi, Tomaso; Van Vugt, Floris Tijmen; Russo, Riccardo (Frontiers in Psychology, 2019)
Little is known about the impact of success and failure events on age-related changes in affect states and, particularly, in self-esteem levels. To fill this gap in the literature, in the present study changes in affect and self-esteem in 100 young (19 - 30 years) and 102 older adults (65-81 years) were assessed after participants experienced success and failure in a demanding cognitive task. Overall, the success-failure manipulation induced changes on affect states and on state self-esteem, not on trait self-esteem. Regarding age differences, older and young adults were affected to the same extent by experiences of successes and failures. Theoretical considerations of the empirical findings are provided in the general discussion.